List of coastal fishes of Islas Marías archipelago, Mexico, with comments on taxonomic composition, biogeography, and abundance - Erisman, Brad E.; Galland, Grantly R.; Mascareñas, Ismael; Moxley, Jerry; Walker, H. J.; Aburto-Oropeza, Octavio; Hastings, Philip A.; Ezcurra, Exequiel (Zootaxa, 2011)
The first comprehensive list of 318 coastal fish species recorded from the Islas Marías Archipelago, Mexico, was compiled from recent fieldwork, archival museum collections, and literature references. The jacks (Carangidae, 18 species) and the labrisomid blennies (Labrisomidae, 16) were the most speciose families. Most recorded species occur throughout the tropical eastern Pacific (160 species), while a significant proportion have wider ranges in the eastern Pacific (39), eastern Pacific and Indo-Pacific (39), eastern Pacific and Atlantic (3), or are circumtropical (39) in distribution. Three species occur in the Northeast Pacific, twenty-five are endemic to the Pacific coasts of Mexico, five are endemic to the Gulf of California, and three are endemic to Islas Marías. Cephalopholis panamensis (Epinephelidae), Epinephelus labriformis (Epinephelidae), Mulloidichthys dentatus (Mullidae), Stegastes flavilatus (Pomacentridae), Acanthurus xanthopterus (Acanthuridae), Pseudobalistes naufragium (Tetraodontidae), and Sufflamen verres (Tetraodontidae) were the dominant conspicuous species observed during underwater surveys in 2010. The absence or low abundance of commercially valuable shark, ray, and grouper species throughout the archipelago is discussed.